2014
DOI: 10.1007/s13224-014-0535-2
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the “Hands-Off” and “Hands-On” Methods to Reduce Perineal Lacerations: A Randomised Clinical Trial

Abstract: Objective The objective of the current study was to compare the ''Hands-off'' and ''Hands-on'' methods to reduce perineal lacerations. Method We conducted a randomized controlled trial to compare the effectiveness of two techniques for perineum protection during spontaneous delivery. Study participants included 600 nulliparous expectant mothers, who were divided equally between the ''hands off'' and ''hands on'' groups (n_300 per group). Findings A total of 147 (49 %) women in the ''Handson'' and 143 women (47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 9 publications
0
7
0
7
Order By: Relevance
“…There was also a change in obstetric practice in a randomized controlled clinical trial with 600 nulliparous women in Iran comparing perineal protection techniques (hands onintervention technique of perineal protection and hands off -expectant technique of perineal protection) by the reduction of perineal traumas. The authors concluded that there were www.ee.usp.br/reeusp Implementation methodology of practices based on scientific evidence for assistance in natural delivery: a pilot study more cases of episiotomy and third-degree perineal lacerations with the hands on technique than hands off (15) . An analysis of the medical records showed that the practicing of non-pharmacological pain relief methods was adopted more after the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…There was also a change in obstetric practice in a randomized controlled clinical trial with 600 nulliparous women in Iran comparing perineal protection techniques (hands onintervention technique of perineal protection and hands off -expectant technique of perineal protection) by the reduction of perineal traumas. The authors concluded that there were www.ee.usp.br/reeusp Implementation methodology of practices based on scientific evidence for assistance in natural delivery: a pilot study more cases of episiotomy and third-degree perineal lacerations with the hands on technique than hands off (15) . An analysis of the medical records showed that the practicing of non-pharmacological pain relief methods was adopted more after the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The advancement of the fetal head, and stretching of the perineum in the minutes before giving birth, are accompanied by pain that can be severe. [16] Midwives utilize a variety of non-pharmacological methods in the second stage of labor, in the belief that these may help lower genital tract trauma and perineal pain including: Hands-on or Hands-off, [17,18] perineal massage, [19] and warm packs. [15] Perineal warm packs or warm compresses have been advocated for many years in the belief that they reduce perineal trauma and increase comfort during late second stage.…”
Section: Introductionmentioning
confidence: 99%
“…Application of the "hands-off" method for vaginal delivery has a positive effect on the mother's health because of the reduction of episiotomy and third-degree tearing. Therefore, it is concluded that the "hands-off" method offers a safer alternative for perineal control during labor [14].…”
Section: Discussionmentioning
confidence: 99%